Ujawnienie i prezentacja zasad (polityki) rachunkowości według Międzynarodowych Standardów Sprawozdawczości Finansowej - Cińcio, Donata (Disclosure and Presentation of Accounting Policies Based on IFRS, 2007)
This report describes selection, adaptation, disclosure and presentation of accounting policy based on International Financial Reporting Standards. From 2005 all publicly traded EU companies are obliged to prepare their consolidated accounts using IFRS. The requirements of accounting policies are contained in Framework for the Preparation and Presentation of Financial Statements, IAS I Presentation of Financial Statements and IAS 8 Accounting Policies, Changes in Accounting Estimates, and Errors. Framework indicates basic principles and grounds of IFRS. IAS 8 states that, when a Standard or an Interpretation specifically applies to a transaction, other event or condition, the accounting policy or policies applied to that item must be determined by applying the Standard or Interpretation and considering any relevant Implementation Guidance issued by the IASB for the Standard or Interpretation. IAS I suggests that in the notes should be presented: the measurement basis (or bases) used in preparing the financial statements and the other accounting policies used in a way that, they are relevant to the understanding of the financial statements.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 196-203